PREPARING OF CHILDREN FOR LEARNING AT NEW UKRAINIAN SCHOOL: PARTNERSHIP INTERACTION OF EDUCATIONAL INSTITUTIONS AND APPLICANTS FOR EDUCATION - Kozyr Marharyta; Tetyana Kalinichenko (Borys Grinchenko Kyiv Metropolitan University, 2021)
The authors reveal the issues of partnership between the preschool institution and the school in preparing children for study at New Ukrainian School. The main condition for ensuring continuity in education and training is determined by the orientation of the educational process of the preschool institution and the New Ukrainian School on the comprehensive development of the child's personality. It is emphasized that the knowledge, skills and experience gained in preschool and family will be used to actively use them in the educational process, as the interest of preschool educational institution and New Ukrainian School will make the transition from preschool to school painless for the child. Emphasis is placed on the fact that partnership in relations between the participants of the educational process is a guarantee of their productive interaction, one of the ways to solve educational problems. The object of the study is the partnership between the preschool and school in preparing children for study at New Ukrainian School; subject of research - preparation of children for study at New Ukrainian School; The purpose of the article is a theoretical substantiation (based on a holistic analysis of scientific sources) and an empirical study of the problem of implementing partnership between preschool and school in preparing children for study in the New Ukrainian School. The authors came to the conclusion that according to the Law of Ukraine «About Education» the aspect of pedagogy of partnership between all participants of the educational process acquires great importance in the Concept of New Ukrainian School. The pedagogy of partnership is based on the principles of humanism and a creative approach to personal development. Its goal is to develop a humane society free from totalitarianism. The New Ukrainian School stipulates that teachers, together with parents, form a partnership centered on the child. The current state of preschool and primary education is characterized by diverse coverage of many issues in the interaction of the pedagogical process of preschool educational institution and New Ukrainian School, and the partnership of related levels of education, i.e. preschool educational institution and New Ukrainian School, will help unite the efforts of preschool educational institution educators, primary school teachers and parents in continuing education.